2017
DOI: 10.5858/arpa.2016-0101-rs
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intraprostatic Synovial Sarcoma

Abstract: Primary intraprostatic synovial sarcoma is a rare presentation of an otherwise well-studied disease, and it is one of the few primary sarcomas to occur in the prostate. Ancillary diagnostic techniques including immunohistochemistry and molecular genetics are useful to establish a definitive diagnosis. Despite its unorthodox location, it shares histologic and molecular genetic characteristics with tumors found elsewhere in the body. Most notably, the chromosomal translocation t(X;18)(p11;q11) encodes a chimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…PRKACA was identified by recent sequencing as a driver of cortisol-producing adenomas and perihilar cholangiocarcinoma [ 41 , 42 ]. SS18 with SSX fusion has been reported as driver of synovial sarcoma in many research studies [ 43 47 ]. TERT has also been reported as a cancer driver of various tissues including thyroid and liver [ 48 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…PRKACA was identified by recent sequencing as a driver of cortisol-producing adenomas and perihilar cholangiocarcinoma [ 41 , 42 ]. SS18 with SSX fusion has been reported as driver of synovial sarcoma in many research studies [ 43 47 ]. TERT has also been reported as a cancer driver of various tissues including thyroid and liver [ 48 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Synovial sarcoma may occur at almost any anatomic site, 5 including the lungs, kidneys, cerebellum, parapharyngeal region, and heart. Cases of intraprostatic synovial sarcoma have also been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial sarcoma is driven by the presence of the t (X; 18) (p11.2; q11.2) translocation, which results in the formation of SS18 subunit of BAF chromatin remodelling complex ( SS18 )-SSX family member ( SSX ) fusion oncogenes. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate comply SS is extremely rare in clinical practice. The first case was reported by Iwasaki et al in 1999 [1] , and we retrieved nine cases in the English literature that were confirmed as primary SS of the prostate by molecular detection methods [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . In the prostate biopsy, a case of prostate SS was found, which was confirmed to be prostate SS by immunohistochemistry and fluorescence in situ hybridization (FISH).…”
Section: Introduction and Importancementioning
confidence: 99%